Genetically diverse mice are novel and valuable models of age-associated susceptibility to Mycobacterium tuberculosis. - Harrison, David E.; Astle, Clinton M.; Niazi, M Khalid.; Major, Samuel.; Beamer, Gillian L. (2016)
Background: Tuberculosis, the disease due to Mycobacterium tuberculosis, is an important cause of morbidity and mortality in the elderly. Use of mouse models may accelerate insight into the disease and tests of therapies since mice age thirty times faster than humans. However, the majority of TB research relies on inbred mouse strains, and these results might not extrapolate well to the genetically diverse human population. We report here the first tests of M. tuberculosis infection in genetically heterogeneous aging mice, testing if old mice benefit from rapamycin.; Keywords: Tuberculosis, Rapamycin, HET3, DO, Diversity outbred, Genetically diverse population, Early Secreted Antigenic Target-6 (ESAT-6).; Springer Open.